HUBUNGAN DINAMIS ANTARA KURS DOLLAR/RUPIAH TERHADAP INDEKS HARGA SAHAM (IHSG) - S, Loriennita Agustina; Indarti, MG Kentris (Jurnal Ilmiah Telaah Manajemen, 2005)
The objective of this research is to find out empirical evidence of the fluctuation that occur on stock price index can be explained by the fluctuation of exchange rate of Rupiah to American Dollar. And the correlation between both. This research examine the correlation between exchange rate of Rupuah to American Dollar by stock price index predicted in sector, LQ 45 index, and thoroughly. The population of this research was thoroughly stock price index, LQ 45 companies, and sector index covering period during 2001-2004.Sample period covering September 1, 2001 to August 30, 2004. The sample continued previous research using periode August 1, 1997 to August 31, 2001. The research hypotheses were tested using Error Correction Model (ECM) and Causality.The result of this research show that in short term generally only occur one stream correlation, stock price correlated negatively to exchange rate. Meanwhile, only stock price index from farm sector has causality to exchange rate in long term. Its correlation is positive.